Serendipitous Synthesis of 5-Hydroxyuridine from 2′,3′-O-Isopropylidene N4-Acetylcytidine by Hypervalent Iodine(III)-Mediated Reaction - Maverick, Mary Anne; Noël, Mathieu; Vasseur, Jean-Jacques; Baraguey, Carine; Debart, Françoise; Smietana, Michael (Synlett, 2023)
Whereas BAIB-TEMPO oxidation of 2′,3′-O-TBDMS-N4-acetylcytidine results in the expected 5′-carboxylic acid nucleoside, its 2′,3′-O-isopropylidene analogue reacts in a radically different way. We have demonstrated here that hypervalent iodine(III) in water triggers an unprecedented oxidative cyclization leading to a mixture of C5-substituted O6,5′-cyclo-5,6-dihydrouridines. This mixture of cyclouridines can be opened under basic conditions and, after deprotection, yields 5-hydroxyuridine, an important post-transcriptional modification of uridine at the wobble position (U34) of bacterial tRNA. NMR experimental values and calculations were performed to provide further insight on the specific reactivity of 2′,3′-O-isopropylidene N4-acetylcytidine.
Keywords: hypervalent iodine; nucleosides; cyclouridine; oxidative cyclization; 5-hydroxyuridine